Unraveling the diversification history of grasshoppers belonging to the "Trimerotropis pallidipennis" (Oedipodinae: Acrididae) species group: A hotspot of biodiversity in the Central Andes - Guzman, Noelia Veronica (2017)
The Andean Mountain range has been recognized as one of the biodiversity hotspotsof the world. The proposed mechanisms for such species diversification, among others, are due to the elevation processes occurring during the Miocene and the intensiveglacial action during the Pleistocene. In this study we investigated the diversificationhistory of the grasshopper Trimerotropis pallidipennis species complex which showsa particularly wide latitudinal and altitudinal distribution range across the northern, central and southern Andes in South America. Many genetic lineages of this complexhave been so far discovered, making it an excellent model to investigate the role of thecentral Andes Mountains together with climatic fluctuations as drivers of speciation. Phylogenetics, biogeographic and molecular clock analyses using a multi-locus datasetrevealed that in Peru there are at least two, and possibly four genetic lineages. Twodifferent stocks originated from a common ancestor from North/Central Americawould have dispersed toward southern latitudes favored by the closure of the PanamaIsthmus giving rise to two lineages, the coastal and mountain lineages, which still coexistin Peru (i.e., T. pallidipennis and T. andeana). Subsequent vicariant and dispersalevents continued the differentiation process, giving rise to three to six genetic lineages(i.e., clades) detected in this study, which were geographically restricted to locationsdispersed over the central Andes Mountains in South America. Our results provideanother interesting example of ``island diversification" motored by the topographyplus unstable climatic conditions during the Pleistocene, pointing out the presence ofa hotspot of diversification in the Andean region of Peru.